Seasonal dynamics of stress perception and coping strategies among Chinese elite Basketball referees - Zhai, Z.; Li, L.; Chen, J.; Zhang, S. (Journal of Sports Sciences, 2025)
This study investigated the seasonal fluctuations in stress perception and coping strategies among Chinese elite basketball referees. A total of 65 referees (14 females and 51 males) from the Chinese Basketball Association (CBA) and the Women` s Chinese Basketball Association (WCBA) participated in a longitudinal study across the 2023-2024 season. Stress perception and coping strategies were assessed using adapted versions of the Sources of Acute Stress Scale for Sports Officials (13 items) and the Referees` Coping Styles Scale (9 items). Repeated-measures ANOVA revealed significant temporal and group differences. CBA referees reported higher levels of interpersonal conflict (IC) and rule execution (RE) than WCBA referees, with stress intensity following an up - down - up pattern, while WCBA referees showed a steady decline in rule execution (RE). In terms of coping, CBA referees shifted from avoidance-cognitive (AC) to approach-oriented (AO) strategies over the season, whereas WCBA referees showed a continuous decline in approach-oriented (AO) coping. These findings highlight the dynamic nature of referees` stress and coping responses across the season and underscore the need for phase-specific psychological support tailored to competition level and league context.